The financial crisis and international trade: the consequences for developing countries - Katrin Berensmann; Clara Brandi (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The introduction of an array of protectionist measures in reaction to the global financial crisis obliges us to continue to closely monitor the development of protectionism and to implement measures to counteract it. Despite the introduction of various protectionist measures during and as a result of the global financial crisis, world trade recovered more quickly than initially expected. Increased demand for imports from developing countries significantly contributed to the rapid recovery of trade. Although compared with the Great Depression of the 1930s considerably fewer protectionist measures have been introduced in the course of the current global financial crisis, an increase in worldwide trade barriers is nonetheless observable. This becomes especially obvious when not only conventional tariff and non-tariff restrictions to trade are considered, but also the more subtle, hidden protectionist measures (“ murky protectionism ”), such as rescuing firms to safeguard national interests or manipulating currencies. Despite all their public commitments to open markets, the G20 countries are the worst perpetrators of protectionism. Germany and other EU Member States, as well as Russia, Argentina, India and Brazil, have imposed the bulk of the protectionist measures. Although less than 1 percent of the international movement of goods is actually affected by crisis protectionism, this low percentage should not obscure the consequences of these trade restrictions for individual goods that seriously affect some countries. The largest exporters – China, the EU and the USA – are hit most by the new trade barriers. Overall, developing and emerging countries are affected by about two-fifths of the decline in exports that is caused by protectionism. Although the Least Developed Countries ( LDCs ) are not the countries most affected by the crisis, a total of 141 protectionist measures have been introduced that also harm these countries. In the future, in light of the risk of a further deterioration of the world economic situation and the danger of a currency war, still greater attention should be paid to protectionist measures and their prevention with regard to developing countries – in particular, because trade is of central importance for their economic development. Crisis protectionism underscores the significance of the World Trade Organization (WTO), and especially how problematic the foreseeable collapse of the Doha Round is that would considerably reduce the leeway for WTO-compliant trade distortions and reversals of market deregulation as a result of this – or future – crises. The WTO's multilateral trade rules should be collectively reinforced so as to more effectively prevent “ murky protectionism ”. For example, the WTO principle of national treatment should be strengthened and the WTO Subsidies Agreement should be reconsidered. The monitoring and control of protectionist measures through independent supervisory institutions like the WTO should be further improved.
Keywords: 330